Breeding quality protein maize (Zea mays): Genetic and analytical perspective - TUFCHI, MAHAK; RASHMI, RASHMI; KUMAR, ARVIND; CHAUDHARY, D P; SINGH, N K; JAT, S L (The Indian Journal of Agricultural Sciences, 2021)
Maize is one of the prominent cereal crops locally as well as internationally for both biological and industrial processing. The nutritional value of maize grains is graded to be poor due to limiting essential amino acids mainly lysine and tryptophan. A series of events beginning by the discovery of the opaque-2 mutation until the development of enhanced protein quality cultivars paved the way for the role of amino acid modifiers genes and proteins. Quality Protein Maize (QPM) is the improved variant of the normal maize with enhanced protein quality. Protein body (PB) formation and the association of the molecular structure of the starch and PB has been a study of concern. Various changes in biochemical pathways leading to the changed zein and non-zein proportions have been studied using transgenic technology which forms an important component of maize protein. Maintaining the quality parameter of QPM inbreds, hybrids and populations so developed is a scientific concern to the speedy and precise determination of quality parameters and further maintaining these parameters using standard breeding methods. The role of biochemist and biochemical techniques are of great significance in maize quality protein research since high throughput and precise nutrient profiling of breeding lines, populations, inbred lines and hybrids support a sound QPM development programme. Various advanced techniques have been developed so far, for the protein isolation till detection and quantification of protein.Among these, the most advanced is the Ultra Performance Liquid Chromatography(UPLC) technique which is highly accurate and can be used efficiently for amino acid profiling of the maize germplasm, breeding lines and hybrids to support the decision making the process in QPM breeding programme. Thus, this review gives us an overview of the breeding methods and biochemical techniques utilized in the development of QPM in the current year 2019 and beyond.